Endoglycosidase and Glycoamidase Release of N-Linked Glycans - Freeze, Hudson H. (2010)
Nearly all proteins entering the lumen of the endoplasmic reticulum (ER) become glycosylated en route to a cellular organelle, the plasma membrane, or the extracellular space. Many glycans can be attached to proteins, but the most common are the N-linked glycans (oligosaccharides). These chains are added very soon after a protein enters the ER, but they undergo extensive remodeling (processing), especially in the Golgi. Processing changes the sensitivity of the N-glycan to enzymes that cleave entire sugar chains or individual monosaccharides, which also changes the migration of the protein on SDS gels. These changes can be used to indicate when a protein has passed a particular subcellular location. This unit details some of the methods used to track a protein as it trafficks from the ER to the Golgi toward its final location.